Geometry of the Poincaré plot can segregate the two arms of autonomic nervous system – A hypothesis. (May 2020) - Roy, Soma; Goswami, Damodar Prasad; Sengupta, Arnab
Abstract: Autonomic Nervous System (ANS) operates to achieve the optimum physiological functioning and maintains homeostasis in a tonic and continuous manner. Evaluation of ANS profile is crucial in assessing autonomic dysfunction. Conventional ANS evaluation procedures fail to capture minute dynamic alterations of ANS activities. The ANS output pattern is appropriately reflected in the fine alteration of the resting heart rate (HR). HR is a non-stationary variable, results from the dynamic interplay between the multiple physiologic mechanisms. The control of cardiac rate or the chronotropic regulation of heart is considered as a coupled network of oscillators, each representing a specific facet of the cardiovascular reflex. The slower vasomotor oscillation via sympathetic system is combined with rapid respiratory oscillation by parasympathetic system to modulate the intrinsic oscillation pattern of the SA Node. Heart Rate Variability (HRV) is used to understand the autonomic influence on cardiovascular system in health and disease. Fourier decomposition of HRV offers us mainly two different frequency components. High frequency (HF) variation indicates parasympathetic variability due to respiration and Low frequency (LF) mainly implicates tonic sympathetic influence, due to slower vasomotor modulation of heart rate. However, different studies show conflicting results and direct recording of sympathetic nerve activity also failed to correlate with LF power in either healthy subjects or in patients with increased cardiac sympathetic drive. A scatter-plot where each R-R interval is plotted against the preceding R-R interval forms a distributed elliptic point cloud in two dimensional plane. The phase space realization of this plot with dimension two and delay one is referred to as Poincaré plot analysis, an emerging quantitative-visual technique where the shape of the plot is categorized into different functional classes. The plot provides summary as well as detailed beat-to-beat information of the heart. This plot can be extended to three dimensions and with multi-lag, offering more insight and information. A mathematical expression was developed by an interventional study by Toichi et al., using pharmacological blockers during different physiological variables that calculated the lengths of transverse and longitudinal axes of the Poincaré plot to derive two quantitative expressions of sympathetic and vagal influence on HRV: 'cardiac sympathetic index' (CSI)) and 'cardiac vagal index' (CVI). In the present study, we emulate Poincaré plot patterns seen in normal range of sympatho-vagal balances and also in Diabetes Mellitus (DM), known to cause autonomic dysfunction. The emerging pattern of R-R interval time series would provide valuable insight into the altered temporal dynamics and also extract crucial features embedded within. DM is a major public health crisis globally and particularly in Indian population. We hypothesize that, CSI and CVI will effectively segregate the two arms of ANS and can be utilized as an effective evaluation tool to explore the disease status in patients of Diabetes Mellitus. We also propose that, the dynamics of fluctuations in physiological rhythms that exhibit long-term correlation and memory, can also be explored and expressed quantitatively by incorporating various degrees of 'lag' in these recurrence plots.